2012
DOI: 10.4049/jimmunol.1102405
|View full text |Cite
|
Sign up to set email alerts
|

Membrane-Tethered MUC1 Mucin Is Phosphorylated by Epidermal Growth Factor Receptor in Airway Epithelial Cells and Associates with TLR5 To Inhibit Recruitment of MyD88

Abstract: MUC1 is a membrane-tethered mucin glycoprotein expressed on the apical surface of mucosal epithelial cells. Previous in vivo and in vitro studies established that MUC1 counter-regulates airway inflammation by suppressing TLR signaling. In this report, we elucidate the mechanism by which MUC1 inhibits TLR5 signaling. Overexpression of MUC1 in human embryonic kidney HEK293 (293) cells dramatically reduced Pseudomonas aeruginosa (Pa)-stimulated IL-8 expression, and decreased the activation of NF-κB and MAPK compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
75
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 56 publications
(81 citation statements)
references
References 48 publications
(68 reference statements)
6
75
0
Order By: Relevance
“…This results in inhibition of TLR signaling and a dampening of airway inflammation. This pathway has been elucidated in TLR5-dependent activation of primary epithelial cells in Pseudomonas aeruginosa infection, 14,15 but is also consistent with findings of negative regulation of other TLR molecules 12 and with the antiinflammatory effect of MUC1 during respiratory syncytial virus infection 13 and Haemophilus influenzae infection 44 of lung epithelial cells in vitro.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This results in inhibition of TLR signaling and a dampening of airway inflammation. This pathway has been elucidated in TLR5-dependent activation of primary epithelial cells in Pseudomonas aeruginosa infection, 14,15 but is also consistent with findings of negative regulation of other TLR molecules 12 and with the antiinflammatory effect of MUC1 during respiratory syncytial virus infection 13 and Haemophilus influenzae infection 44 of lung epithelial cells in vitro.…”
Section: Discussionsupporting
confidence: 84%
“…In response to airway infection by Pseudomonas aeruginosa 12 and respiratory syncytial virus, 13 TLR activation in airway epithelial cells and macrophages induces the production of inflammatory mediators such as IL-8 (KC in the mouse) and TNFa to recruit effector cells. 14,15 In turn, MUC1 is upregulated and acts to suppress TLR signaling. 16 In addition, production of the antiinflammatory IL-10 and type I interferon (IFN) has been shown to correlate with increased MUC1 expression.…”
Section: Introductionmentioning
confidence: 99%
“…Muc1 Ϫ/Ϫ mice experimentally infected in the stomach with H. pylori or in the lungs with P. aeruginosa or respiratory syncytial virus, had higher levels of TNF-␣ and KC (murine IL-8) and enhanced NF-B activation in the respective epithelia compared with Muc1 ϩ/ϩ littermates. These effects appeared to be mediated through the action of the MUC1 cytoplasmic domain and, more specifically, by one or more of the potential intracellular tyrosine phosphorylation sites, since anti-inflammatory activity was lost using an intracellular tyrosine deficient MUC1 mutant (24). Similar studies by others confirmed that murine MUC1 also counterregulates inflammatory responses against Staphylococcus, Streptococcus, and Corynebacterium, although the responsible mechanism was not described (21).…”
Section: ϫ/ϫ (Iii Iv) Mice Following Inoculation With Pbs Vehicle Cosupporting
confidence: 64%
“…In gastric epithelia, MUC1 contributes to the physicochemical barrier against infectious pathogens (12). On airway epithelial cells, MUC1-EC is an adhesion site for Pseudomonas aeruginosa (Pa) (13,14), whereas MUC1-CT interacts with Toll-like receptors (TLRs) (15,16). Binding of MUC1-CT to TLR5 competitively inhibits recruitment of MyD88 to the TLR5 cytosolic Toll/IL-1 receptor domain, thereby suppressing TLR5 signaling and downstream inflammatory responses (15).…”
mentioning
confidence: 99%
“…On airway epithelial cells, MUC1-EC is an adhesion site for Pseudomonas aeruginosa (Pa) (13,14), whereas MUC1-CT interacts with Toll-like receptors (TLRs) (15,16). Binding of MUC1-CT to TLR5 competitively inhibits recruitment of MyD88 to the TLR5 cytosolic Toll/IL-1 receptor domain, thereby suppressing TLR5 signaling and downstream inflammatory responses (15). After experimental Pa lung infection, Muc1 null mice mount hyperinflammatory airway responses and exhibit enhanced bacterial clearance from the lungs compared with wild-type (WT) mice (17).…”
mentioning
confidence: 99%